Pattern of Bacterial Infections in Paediatric Patients with Chemotherapy-Induced Neutropenia - Chaudhry, Shakeel Ahmad; Ghafoor, Tariq; Batool, Syeda Maher; Khalil, Sumaira; Farah, Tanzeela (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To determine the frequency of bacterial infections and their sensitivity to various antibiotics in paediatric cancer patients having chemotherapy-induced neutropenia.Study Design: Cross-sectional studyPlace and Duration of Study: Paediatric Oncology ward, Combined Military Hospital, Rawalpindi Pakistan, from Jul 2018 to Jan 2019.Methodology: A total of 205 children aged one year to 12 years undergoing chemotherapy and having neutropenic fever were included. Complete history, full physical examination and related blood, microbiological and radiological investigations were undertaken. Antibiotics were given as per protocol.Results: In our study, the bacterial infections in paediatric cancer patients with chemotherapy-induced neutropenia was found in 45(21.95%) patients. Of these, gram-positive organisms were found in 25(55.5%) patients and gram-negative in 20(44.4%).Conclusion: The frequency of bacterial infections in paediatric patients with chemotherapy-induced febrile neutropenia is quite high, with a high percentage of gram-positive bacteria.